2007
DOI: 10.1111/j.1365-2249.2007.03471.x
|View full text |Cite
|
Sign up to set email alerts
|

Extremes of l-ficolin concentration in children with recurrent infections are associated with single nucleotide polymorphisms in the FCN2 gene

Abstract: Summaryl-ficolin (also called ficolin-2, P35 or hucolin) is a soluble pattern recognition molecule of suspected importance in anti-microbial immunity. It activates the lectin pathway of complement and acts as an opsonin. l-ficolin, encoded by the FCN2 gene, recognizes microbial polysaccharides and glycoconjugates rich in GlcNAc or GalNAc. We report here data concerning four single nucleotide polymorphisms (SNPs) of the FCN2 gene and their relationship to l-ficolin serum concentrations. There are two pairs of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 21 publications
2
45
0
5
Order By: Relevance
“…Much like MBL, L-ficolin has been observed to be present in the bronchoalveolar lavage fluid following inflammation (J. D. Chalmers, personal communication; 37). L-Ficolin gene polymorphisms and insufficiencies have been acknowledged to have implications for allergic inflammation and recurrent respiratory infections (38,39). We therefore investigated whether ficolin-A and L-ficolin could modulate the association of A. fumigatus conidia with A549 airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Much like MBL, L-ficolin has been observed to be present in the bronchoalveolar lavage fluid following inflammation (J. D. Chalmers, personal communication; 37). L-Ficolin gene polymorphisms and insufficiencies have been acknowledged to have implications for allergic inflammation and recurrent respiratory infections (38,39). We therefore investigated whether ficolin-A and L-ficolin could modulate the association of A. fumigatus conidia with A549 airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Krarup et al [21] showed that L-ficolin binds to some capsulated S t reptococcus pneumoniae serotypes. Cedzynski et al [42] estimated serum L-ficolin concentrations in children with recurrent respiratory infections and predicted that high L-ficolin concentrations could confer enhanced protection from some infectious disorders. In this study, we found that the collectin molecule L-ficolin bound the envelope glycoproteins HA and NA and that L-ficolin enhanced mouse resistance to the influenza A virus.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike MBL2 polymorphisms, which produce substantial variation in the concentration and function of MBL over a 1,000-fold range, ficolin levels in the presence of these FCN2 and FCN3 polymorphisms vary at most by only a factor of 20 [74,75] , with no absolute deficiency identified. Associations between FCN2 [76] and FCN3 [74] single nucleotide polymorphisms and low or high serum levels are becoming apparent.…”
Section: Molecular and Clinical Comparisons Between Ficolins And Mblmentioning
confidence: 99%